2005
DOI: 10.1105/tpc.105.031229
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of a Cyanobacterial Sucrose-Phosphatase Reveals the Sugar Tongs That Release Free Sucrose in the Cell

Abstract: Sucrose-phosphatase (SPP) catalyzes the final step in the pathway of sucrose biosynthesis in both plants and cyanobacteria, and the SPPs from these two groups of organisms are closely related. We have crystallized the enzyme from the cyanobacterium Synechocystis sp PCC 6803 and determined its crystal structure alone and in complex with various ligands. The protein consists of a core domain containing the catalytic site and a smaller cap domain that contains a glucose binding site. Two flexible hinge loops link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(107 citation statements)
references
References 38 publications
5
102
0
Order By: Relevance
“…The phosphatase domain of all these proteins includes three amino acid motifs that are characteristic of the L-2-haloacid dehalogenase (HAD) superfamily of enzymes: motif I -DX(D/T/Y)X(T/V)(L/V/I), motif II -a Ser or Thr, generally in a hydrophobic context, and motif III -KX 18-30 (G/S)(D/S)X 3 (D/N). Motif I is the most highly conserved, and the invariant first Asp is the functional nucleophile that forms a phospho-acyl intermediate during catalysis (Fieulaine et al 2005). The HAD superfamily embraces a wide range of phosphatases and hydrolases, including the analogous enzyme of sucrose synthesis, sucrosephosphatase (Lunn et al 2000), and crystal structures show that the three conserved motifs form the active site of HAD superfamily enzymes (Fieulaine et al 2005;Burroughs et al 2006).…”
Section: Myrothamnus Flabellifolius Welw and Sporobolus Atrovirensmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphatase domain of all these proteins includes three amino acid motifs that are characteristic of the L-2-haloacid dehalogenase (HAD) superfamily of enzymes: motif I -DX(D/T/Y)X(T/V)(L/V/I), motif II -a Ser or Thr, generally in a hydrophobic context, and motif III -KX 18-30 (G/S)(D/S)X 3 (D/N). Motif I is the most highly conserved, and the invariant first Asp is the functional nucleophile that forms a phospho-acyl intermediate during catalysis (Fieulaine et al 2005). The HAD superfamily embraces a wide range of phosphatases and hydrolases, including the analogous enzyme of sucrose synthesis, sucrosephosphatase (Lunn et al 2000), and crystal structures show that the three conserved motifs form the active site of HAD superfamily enzymes (Fieulaine et al 2005;Burroughs et al 2006).…”
Section: Myrothamnus Flabellifolius Welw and Sporobolus Atrovirensmentioning
confidence: 99%
“…Motif I is the most highly conserved, and the invariant first Asp is the functional nucleophile that forms a phospho-acyl intermediate during catalysis (Fieulaine et al 2005). The HAD superfamily embraces a wide range of phosphatases and hydrolases, including the analogous enzyme of sucrose synthesis, sucrosephosphatase (Lunn et al 2000), and crystal structures show that the three conserved motifs form the active site of HAD superfamily enzymes (Fieulaine et al 2005;Burroughs et al 2006). The presence of these motifs in the class II isoforms of TPS prompted speculation that they might have TPP activity (Leyman et al 2001), but no such activity has been found.…”
Section: Myrothamnus Flabellifolius Welw and Sporobolus Atrovirensmentioning
confidence: 99%
“…PCC 6803 SPP complexed with Suc-6P, shows that the hexose 2-hydroxyl group of the Suc-6P molecule, the only feature that discriminates Suc-6P from MF-6P (Fig. 1), is not involved in the interactions with the disaccharide binding site (16).…”
Section: Discussionmentioning
confidence: 98%
“…Sucrose phosphate synthases similarly have a non functional SPP domain which was proposed to serve the purpose of substrate channeling (Fieulaine et al, 2005), but in the case of TPS it could also serve to sequester T6P. The AtTPS1 enzyme is special because of an N-terminal extension, which is not found in other Arabidopsis TPSs and was shown to mediate regulation of TPS activity; it is also found in the SlTPS1 from Selaginella lepidophylla, a desert resurrection plant that accumulates large amounts of trehalose (Van Dijck et al, 2002).…”
Section: Protein Structures and Possible Functions Of Different Genesmentioning
confidence: 99%